Nerve growth factor rapidly stimulates tyrosine phosphorylation of phospholipase C-gamma 1 by a kinase activity associated with the product of the trk protooncogene. - Vetter, M L (1991)
Nerve growth factor (NGF) promotes the survival and differentiation of specific populations of neurons. The molecular mechanisms by which cells respond to NGF are poorly understood, but two clues have emerged recently. First, NGF rapidly stimulates tyrosine phosphorylation of several unidentified proteins in the NGF-responsive pheochromocytoma cell line PC12 [Maher, P. (1988) Proc. Natl. Acad. Sci. USA 85, 6788-6791]. Second, the protein-tyrosine kinase encoded by the protooncogene trk (p140trk), a member of the receptor class of tyrosine kinases, becomes activated and phosphorylated on tyrosine after NGF treatment of PC12 cells [Kaplan, D. R., Martin-Zanca, D. & Parada, L. F. (1991) Nature (London) 350, 158-160]. We now report that NGF rapidly induces tyrosine phosphorylation of phospholipase C-gamma 1 (PLC-gamma 1), and we present evidence that the responsible tyrosine kinase is either p140trk or a closely associated protein. Treatment of responsive cells with NGF elicited phosphorylation of PLC-gamma 1 on tyrosine and serine. PLC-gamma 1 immunoprecipitated from NGF-stimulated cells was phosphorylated in vitro by coprecipitating protein kinase activity, and the phosphorylations occurred principally on tyrosine. The responsible kinase could be depleted from cellular lysates by antibodies specific for p140trk. This procedure also depleted a 140-kDa protein that normally coprecipitated with PLC-gamma 1 and became phosphorylated on tyrosine in vivo in response to NGF. Analysis of tryptic peptides from PLC-gamma 1 indicated that the residues phosphorylated in vitro by p140trk-associated kinase activity were largely congruent with those phosphorylated in vivo after NGF treatment. Our findings identify PLC-gamma 1 as a likely substrate for the trk-encoded tyrosine kinase, and they provide a link between NGF-dependent activation of p140trk and the stimulation of intracellular second messenger pathways.